Evolution characteristics of dynamic balance disorder over the course of PD and relationship with dopamine depletion - Gan, Jing; Wu, Xiaodong; Wan, Ying; Zhao, Jiahao; Song, Lu; Wu, Na; Wang, Hui; Yin, Yafu; Liu, Zhenguo (Frontiers in Aging Neuroscience, 2023)
Objective This study aimed to assess the evolution of dynamic balance impairment during the course of Parkinson's disease (PD) and to clarify the contribution of striatal dopaminergic innervation to poor dynamic balance. Methods In our study, 89 patients with PD (divided into 2 groups according to the H-Y stage) and 39 controls were included. Kinematic data were recorded by a portable inertial measurement unit system. Dopaminergic loss in the striatal subregion was verified through the 11C-CFT PET examination. The severity of white matter hyperintensities (WMHs) was assessed by the Scheltens scale. The correlation between dynamic kinematic parameters and dopamine transporter availability was analyzed by multivariate regression analysis. Results Patients with early PD presented with imbalance featured by smaller three-dimensional trunk ROM with reduced trunk coronal angular velocity during walking and with reduced trunk sagittal angular velocity during the stand-to-sit task (all p < 0.05). These abnormalities were not more severe at a later stage. The ROM in the coronal and transverse planes during walking correlated with caudate DAT uptake (β = 0.832, p = 0.006, Q = 0.030, and β = 0.890, p = 0.003, Q = 0.030) after controlling for age, gender, and WMHs. As the disease progressed, the trunk sagittal and transverse angular velocities during walking and trunk sagittal angular velocity when turning and sitting-to-standing were slower, which was accompanied by reduced gait velocity gradually (all p < 0.05). These parameters related to disease progression have no association with striatal DAT uptake (all p > 0.05). Conclusion The dynamic balance in PD was impaired from the early stages, and the characteristics of the impairment changed differently as the disease progressed. Dopaminergic denervation has a lower contribution to dynamic balance disorders throughout PD.